Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kepemimpinan pada PT Matoga Cipta Indonesia Kabupaten Deli Serdang - Mutiah Dwi Arisa; Kiki Farida Ferine; Teguh Wahyono (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the influence of organizational culture and work discipline on leadership at PT Matoga Cipta Indonesia. The research employed a quantitative approach with a population and sample consisting of 40 employees. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that organizational culture has a positive and significant effect on leadership, as indicated by a t-value of 4.086, which is greater than the t-table value of 2.021, and a signifi cance value of 0.000 < 0.05. Work discipline also has a positive and significant effect on leadership, with a t-value of 2.281, exceeding the t-table value of 2.021, and a significance value of 0.028 < 0.05. Simultaneously, both variables significantly influence leadership, as shown by an F-value of 15.506, which is higher than the F-table value of 3.25, and a significance value of 0.000 < 0.05. This study concludes that effective leadership is influenced by strong organizational culture and good work discipline. Therefore, the company should maintain a positive family-oriented culture while enhancing professionalism and work discipline to maximize leadership effectiveness.